KEADILAN DALAM PERJANJIAN KREDIT PERBANKAN - Rudyanti Dorotea Tobing (Jurnal Ilmu Hukum Tambun Bungai, 2016)
Banking financial institution has a strategic role in national development, especially in economic activities, because the bank's main function is to collect and distribute public funds. In the modern business activities, credit is the most important source of financing, it is seldom a business activity rely entirely on internal sources of financing in the form of equity participation (self-financing). Credit is the provision of money or bills can be equated with it, based on agreements between bank lending and other parties who require the borrower to repay their debts after a certain period of time with interest. Giving credit means giving confidence to the debtor by the creditor even though the trust contains a high risk. The crediet agreement arising in practice based on the principle of freedom of contract. The crediet agreement that is based on freedom of contract and only promote the principles of prudence and efficiency, will eventually lead to injustice for the people. Credit only promote economic justice, yet to be realized in national development is social justice.